Применение фундаментальных принципов природы к социальной системе - Толкачев, A. M.; Сидоренко, И. И. (НТУ "ХПИ", 2010)
The similar behavior of social and physical systems in relation to fundamental principles is shown. The main principle provides preservation of the base state of system. Other principles establish system development and its resistance.
Keywords: организация; физическая система; энтропия; детерминированный характер